Effects of smart grid communication networks in distributed generation dispatch (2012)
One of the key aspects in the development of smart grids is the design of bidirectional, real time communication networks in all the fields of the power grid, from the generation to distribution, and including the customer interaction. Because of that, new control and dispatch strategies need to be developed in order to deal with the different issues that are induced by the communication network, such as delays and packet dropouts. This work overviews the smart grid communication network architecture with some of the main characteristics and elements, and the degrading effects of wired and wireless communication networks in an optimal evolutionary dispatch technique are illustrated, using a novel simulation tool that includes the power system dynamics and the communication network infrastructure. Besides, a delay compensation method that solves the delayed dispatch problem is developed for centralized dispatch control.